Chemical modelling of N-bearing COMs in star-forming regions. Issue Volume 13:Issue S332(2017) (4th September 2018) - Quénard, David; Jiménez-Serra, Izaskun; Viti, Serena; Holdship, Jonathan
Abstract: The study of complex organic molecules, and more specifically those of prebiotic interest, is important to understand the chemical richness of star-forming regions. The chemistry of nitrogen bearing molecules such as formamide or methyl isocyanate is poorly constrained. We study different chemical pathways to form and destroy these molecules from both the gas phase and grain surface chemistry. From comparison with observations of four different relevant astrophysical regions, we show that both the gas phase and grain surface chemistry are required to explain the observed abundances of these species.